Self-Efficacy as a Mediator between Financial Autonomy and Educational Support in Enhancing University Students’ Motivation - Jamal Adri; Sandi Sandi; Andi Emil Salim (Indonesian Journal of Business and Entrepreneurship Research, 2025)
This study aims to examine the influence of entrepreneurship education on student motivation through self-efficacy, as well as the impact of financial autonomy on student motivation with self-efficacy as a mediating variable. The research was conducted at the Faculty of Economics and Business, Universitas Negeri Makassar, involving students participating in entrepreneurship education programs. A quantitative approach was employed using a descriptive-explanatory research design. Data was collected through structured questionnaires distributed to 96 randomly selected respondents, and analyzed using path analysis techniques. The findings reveal that entrepreneurship education has a significant and positive influence on student motivation, mediated by self-efficacy. This indicates that quality entrepreneurship education enhances students’ self-confidence, which in turn boosts their motivation to succeed academically and entrepreneurially. Furthermore, financial autonomy also shows a positive effect on student motivation through the enhancement of self-efficacy, suggesting that students with greater financial independence tend to exhibit higher self-belief and stronger motivation to achieve both academic and entrepreneurial goals. These results highlight the essential role of self-efficacy as a bridge connecting educational and financial support to student motivation in higher education contexts.